1988
DOI: 10.1084/jem.167.1.219
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human interleukin 5 is a selective activator of human eosinophil function.

Abstract: Human rIL-5 was found to selectively stimulate morphological changes and the function of human eosinophils. This molecule is thus a prime candidate for the selective eosinophilia and eosinophil activation seen in disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
416
0
9

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 911 publications
(433 citation statements)
references
References 20 publications
8
416
0
9
Order By: Relevance
“…Increased production of cytokines such as IL-4 by the Th2-like cells is critical in the induction of IgE synthesis and maintenance of established ongoing IgE response [21], and also contributes to the orchestration and perpetuation of the allergic inflammatory process [22,23]. Increased attention has recently turned to the possibility that the clinical efficacy of immunotherapy might be elaborated with alteration of T helper-cell activity and cytokine profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Increased production of cytokines such as IL-4 by the Th2-like cells is critical in the induction of IgE synthesis and maintenance of established ongoing IgE response [21], and also contributes to the orchestration and perpetuation of the allergic inflammatory process [22,23]. Increased attention has recently turned to the possibility that the clinical efficacy of immunotherapy might be elaborated with alteration of T helper-cell activity and cytokine profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that absence of CD7 defines a CD4 + T cell subset with a Th0/Th2-like cytokine profile. Since IL-5 is another Th2-related cytokine which is produced by T cells exhibiting a Th2 phenotype [14], we evaluated the profile of IL-5 production in CD7 -cells. Here we show that CD4 + CD7 + and CD4 + CD7 -T cells differ in their capacity to secrete distinct cytokines, and the CD4 + CD7 -fraction, particularly, produces high amounts of IL-5 upon activation in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The demonstration of eosinophil major basic protein and eosinophil derived neurotoxin indicating degranulation at sites of injury are an important part of the evidence that eosinophils are producing tissue damage in the asthmatic lung (Sur et al 1995). Hence, the current evidence suggests that the local production of IL-5 in asthmatic airways may play an important role in the priming of eosinophils for subsequent activation, and in enhancing their survival at sites of allergic inflammation (Lopez et al 1988, Yamaguchi et al 1988, all of which is likely to be important in asthma.…”
Section: Asthma and Il-5 Human Studies: Il5 Mrna And Proteinmentioning
confidence: 94%
“…It activates mature eosinophils and prolongs their survival in culture (Yamaguchi et al 1988)-possibly via its ability to delay apoptosis , as well as selectively enhancing eosinophil degranulation, antibody-dependent cytotoxicity and adhesion to vascular endothelium (Lopez et al 1988, Fujisawa et al 1990). IL-5 enhances the capacity of eosinophils to release LTC4 (Weller et al 1992) and also primes basophils, leading to increased histamine and LTC4 generation (Bischoff et al 1990, Laviollette et al 1995 and increases synthesis of IgM, IgA, IgE by B cells costimulated with IL-4 (Pene et al 1988, Purkerson & Isakson 1992.…”
Section: Il-5 T Cells and Eosinophilsmentioning
confidence: 99%